Relationship of Nurse Support to Quality of Life of Cancer Patients Breasts undergoing chemotherapy in the gull ward RSPAU Dr. S Hardjolukito Yogyakarta - Ulfa Jumrotin Abutalib; Dian Nur Adkhana Sari; Niken Setyaningrum; Endar Timiyatun (Caring : Jurnal Keperawatan, 2021)
Breast Cancer is a type of malignant tumor that develops in breast cells. This cancer can grow if there is abnormal growth of cells in the breast. These cells divide faster than normal cells and accumulate, which then forms a lump or mas,The incidence of breast cancer. 161.682 people. Beast cancer has a great impact on sufferers both physically, psychologically and socially which will affect their quality of life. To support the quality of life of breast cancer patients, they need nurse support.Nurse care to motivate patient so that patient do not experience stress and the depression for the illness.To find out whether there is a relationship between nurse support and the quality of life of breast cancer patients undergoing chemotherapy at RSPAU Dr. Hardjolukito Yogyakarta.This research is a quantitative non-experimental research. population in this study were all breast cancer patients who underwent chemotherapy in the Gull ward totaling 109. Samples in were 52 respondents with non-probability sampling using purposive sampling technique. ResultsBased moderate category were 29 respondents 55.8%), and the quality of life of breast cancer patients in the good category was 46 respondents (88.5%). From the Kendalls Tau test results obtained P value = 0,000 with an alpha value of P = 0.05, then the P value <P value alpha (0,000 <0.05) so that nurse support has a relationship to the quality of life of breast cancer patients.Conclusion There is a relationship between nurses' support and the quality of life of breast cancer patients at RSPAU Dr. S.Hardjolokito Yogyakarta.